Role of surface activity in the biological actions of ranitidine and famotidine - Pandi, P.V.; Kole, P.L.; Mishra, P.K.R.; Shanmukha, I.; Girish, K.; Nagappa, A.N. (2004)
The role of surface activity has been studied in the biological actions of ranitidine (RNT) and famotidine (FMT). The drugs have been shown to generate liquid membranes in series with a supporting membrane with the virtue of their amphiphilicity. Transport of histamine, acetylcholine, and ions (chloride, bicarbonate, potassium, sodium and calcium) have been studied in the presence of liquid membranes generated by surface-active RNT and FMT. The data on the modifications in the permeability of histamine, acetylcholine and ions indicate that the liquid membranes generated by RNT and FMT may play a significant role in their biological action. The surface-active nature of the drugs has been discussed with relevance to their pharmacological effects. (C) 2004 Elsevier B.V. All rights reserved.